Practical pedagogy 40 new ways to teach and learn - Sharples, Mike 1952- (Routledge, 2019)
Practical Pedagogy expands the universe of teaching and learning. It provides an accessible guide to new and emerging innovations in education, with insights into how to become more effective as a teacher and learner. New teachers will find a comprehensive introduction to innovative ways of teaching and learning. Experienced educators will be surprised by the range of useful pedagogies, such as translanguaging, crossover learning, teachback, bricolage and rhizomatic learning. Policy makers will gain evidence of how new teaching methods work in practice, with resources for curriculum design and course development. Drawing on material from the hugely influential Innovating Pedagogy series of reports, this book is a compilation of the 40 most relevant pedagogies, covering: innovative ways to teach and learn; how pedagogies are adopted in new ways for a digital age; evidence on how and why different methods of teaching work, including case studies set in classrooms, informal settings, and online learning spaces; practical implications of the latest research into the science of learning, combining psychology, education, social sciences and neuroscience. Organised around six themes - Personalization, Connectivity, Reflection, Extension, Embodiment and Scale - Practical Pedagogy is a comprehensive source for teachers, policy makers, educational researchers and anyone interested in new ways to teach and learn